I'll take the low road: the evolutionary underpinnings of visually triggered fear - Carr, James A. (Frontiers in Neuroscience, 2015)
Although there is general agreement that the central nucleus of the amygdala (CeA) is critical for triggering the neuroendocrine response to visual threats, there is uncertainty about the role of subcortical visual pathways in this process. Primates in general appear to depend less on subcortical visual pathways than other mammals. Yet, imaging studies continue to indicate a role for the superior colliculus and pulvinar nucleus in fear activation, despite disconnects in how these brain structures communicate not only with each other but with the amygdala. Studies in fish and amphibians suggest that the neuroendocrine response to visual threats has remained relatively unchanged for hundreds of millions of years, yet there are still significant data gaps with respect to how visual information is relayed to telencephalic areas homologous to the CeA, particularly in fish. In fact ray finned fishes may have evolved an entirely different mechanism for relaying visual information to the telencephalon. In part because they lack a pathway homologous to the lateral geniculate-striate cortex pathway of mammals, amphibians continue to be an excellent model for studying how stress hormones in turn modulate fear activating visual pathways. Glucocorticoids, melanocortin peptides, and CRF all appear to play some role in modulating sensorimotor processing in the optic tectum. These observations, coupled with data showing control of the hypothalamus-pituitary-adrenal axis by the superior colliculus, suggest a fear/stress/anxiety neuroendocrine circuit that begins with first order synapses in subcortical visual pathways. Thus, comparative studies shed light not only on how fear triggering visual pathways came to be, but how hormones released as a result of this activation modulate these pathways.